Transformative Learning and Identity: A review and synthesis of Dirkx and Illeris - Cheryl K Baldwin (Adult Education Research Conference, 2019)
This review explores transformative learning and identity focusing on the works of John Dirkx and Knud Illeris. The synthesis creates a theoretical framework for research and continuing professional education practice.
Keywords: Transformative Learning; Identity; Identity Transformation